HUBUNGAN PENGETAHUAN TENTANG SADARI DENGAN SIKAP SADARI PADA WANITA DI DESA BANTARWUNI WILAYAH KERJA PUSKESMAS KEMBARAN I KABUPATEN BANYUMAS - Rahmaya Nova Handayani; Feti Kumala Dewi; Evi Dayanti (Viva Medika, 2009)
The majority of breast cancer patients come to medical service at an advancedstage. Because most cancer cases are found in the severe stage, healing is difficult to do. Infact, detection of early-stage breast cancer is very easy, and can be done individually. Quitea few minutes, once a month, to perform breast self-examination (SADARI). But because ofthe level of knowledge of women about cancer remains low so that it can become anobstacle to efforts to prevent the occurrence of breast cancer. To find out knowledgerelations about SADARI with SADARI attitude on women in the Bantarwuni Village,Puskesmas Kembaran's working area, Banyumas District . This research is a descriptiveresearch with cross sectional correlation's study, the sample used was cluster sampling. Thesample was women aged 20-35 years in the Bantarwuni Village, the sample in this researchwas 60 respondents. Instrument of data collection using questionnaires. Data analysisusing Bivariate analysis with statistical test used was chi square. From the results, most ofthe knowledge of knowing about SADARI was less by 28 respondents (47%), and most ofthe negative attitude of knowing it was a total of 36 respondents (60%). There is knowledgerelations about SADARI with SADARI attitude on women in the Bantarwuni Village,Puskesmas Kembaran's working area, Banyumas Distric twith Ã¾-value (0.001) <Î± (0,05).There is knowledge relations about SADARI with SADARI attitude on women in theBantarwuni Village, Puskesmas Kembaran's working area, Banyumas District. Keyword : Knowledge, attitude, SADARI.